2021
DOI: 10.1080/16878507.2021.1964314
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and spatial distribution pattern of natural radioactivity in a uranium tailings pond in Northwest China

Abstract: Numbers of radioactive tailings were produced in the process of uranium mining and milling.In this study,radiation environment monitoring was carried out on a decommissioned uranium mining and milling tailings pond in northwest China, and the governance effect and operation status of the tailings pond was investigated. The soil radionuclide activity concentration and ambient dose equivalent rate (H * (10)) were measured, and soil surface radon exhalation rate was calculated. The results shown that in the taili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…For example, the excessive rate of As in rice planted around some uranium mining areas has reached 97.73% [18]. In addition, the extraction and recovery of radionuclides and heavy metals/metalloids from waste materials are also facing several constraints such as technic-economic, environmental, and social aspects [19]. Thus, a large number of uranium tailings ponds are built to bury the waste materials to prevent radionuclide and heavy metal/metalloid migration and diffusion to the surrounding environment media and maintain long-term stabilization [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the excessive rate of As in rice planted around some uranium mining areas has reached 97.73% [18]. In addition, the extraction and recovery of radionuclides and heavy metals/metalloids from waste materials are also facing several constraints such as technic-economic, environmental, and social aspects [19]. Thus, a large number of uranium tailings ponds are built to bury the waste materials to prevent radionuclide and heavy metal/metalloid migration and diffusion to the surrounding environment media and maintain long-term stabilization [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a large number of uranium tailings ponds are built to bury the waste materials to prevent radionuclide and heavy metal/metalloid migration and diffusion to the surrounding environment media and maintain long-term stabilization [20][21][22]. Nevertheless, with the increasing number of service years of the tailings ponds and the existence of some adverse conditions such as natural or anthropogenic factors, the treated radionuclides and heavy metals/metalloids in the tailings pond still have potential risk of migration and diffusion to the adjacent environment and transfer to the food chain, affecting human health [5,19,23]. Therefore, in view of the characteristics of radionuclides and heavy metals/metalloids in the ecological environment, uranium tailings ponds have attracted extensive attention of researchers and governments all over the world [11,19,20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above approximately after the 1970s onwards (after intensified mining era) most radon and uranium studies were found to concentrate on reporting radiological background, risk estimation and their correlation [18][19][20][21][22][23][24][25][26]. Several relevant papers estimating radon and uranium concentrations of a particular region or site were reported till date [27][28][29][30][31][32][33][34][35][36]. Recent reporters like Bezuidenhout [27] performed mapping and estimation of radon risk in South Africa while Novikov et al [28] reports radon and uranium content in groundwater of the Zaeltsovsky-Mochishch zone of Novosibirsk in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [29] directly measure uranium content in order to map radon hazard region in Norway. Authors like Liu et al in southern China [30], Fuhrmann et al [31] in the USA and Yong et al [32] in northwest China measured radon exhalation rate and fluxes from uranium tailing pond to determine whether it lies within world natural background. All other papers [33][34][35][36] mainly focus on reporting radon and uranium concentrations in soil, water and air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation